Comparison of Rapid Methods for Analysis of Bacterial Fatty Acids - Moss, C. Wayne (1974)
When rapid gas-liquid chromatography methods for determination of bacterial fatty acids were compared, results showed that saponification was required for total fatty acid analysis. Transesterification with boron-trihalide reagents (BF(3)-CH(3)OH, BCl(3)-CH(3)OH) caused extensive degradation of cyclopropane acids and was less effective than saponification in releasing cellular hydroxy fatty acids. Digestion of cells with tetramethylammonium hydroxide was unsatisfactory because of extraneous gas-liquid chromatography peaks and because of lower recovery of branched-chain and hydroxy fatty acids. A simple, rapid saponification procedure which can be used for total cellular fatty acid analysis of freshly grown cells is described.